2023
DOI: 10.1186/s12872-023-03413-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and imaging differences between Stanford Type B intramural hematoma-like lesions and classic aortic dissection

Abstract: Background Intramural hematoma (IMH) and Aortic dissection (AD) have overlapping features. The aim of this study was to explore the differences between them by comparing the clinical manifestations and imaging features of patients with acute Stanford type B IMH-like lesions and acute Stanford type B AD (ATBAD). Methods This study retrospectively analysed the clinical and computed tomography angiography (CTA) imaging data of 42 IMH-like lesions pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Of the 38 IMH patients reported by Kitai et al ( 15 ), 23.7% had intimal defects. In the study by Wei et al ( 16 ), ULP was found in 23.81% of IMH patients during the initial CTA examination. In our study, 42 patients had ULP detected during the first CTA scan, with a detection rate of 21.3%, which is consistent with previous findings.…”
Section: Discussionmentioning
confidence: 92%
“…Of the 38 IMH patients reported by Kitai et al ( 15 ), 23.7% had intimal defects. In the study by Wei et al ( 16 ), ULP was found in 23.81% of IMH patients during the initial CTA examination. In our study, 42 patients had ULP detected during the first CTA scan, with a detection rate of 21.3%, which is consistent with previous findings.…”
Section: Discussionmentioning
confidence: 92%